Effect of fiber in enhancement of mechanical properties and structural behaviors of oil palm shell concrete / Yap Soon Poh - Yap, Soon Poh (2015)
The significance contribution of utilizing locally available waste materials to replace conventional concrete materials gained considerable attention during the past two decades in the realization of sustainable building materials. One such industrial waste material available abound in South East Asia is lightweight oil palm shell (OPS). Earlier researches on OPS showed that OPS could be considered as an ideal replacement of granite aggregates to produce a sustainable lightweight concrete called oil palm shell concrete (OPSC). The development of OPSC has the advantage as a lightweight concrete in addition to environmental benefits. However, the application of OPSC in structural members is less convincing due to its low tensile strength and the addition of fibers has been effective to solve this weakness. The initial challenge in the development of oil palm shell fiber reinforced concrete (OPSFRC) lies in selection of appropriate fibers. In this study, fibrillated and monofilament fibers, nylon fibers and steel fibers of aspect ratio 55, 65 and 80 were added in the OPSC to investigate the effects of different fibers on the mechanical properties of OPSFRC and thereby to select the suitable type of fiber. This would enable to study the effect of volume fraction of fibers on the mechanical properties and structural behaviors under flexural and torsion. In addition, by using a high volume fraction of 3% of steel fibers was added in OPSC to further enhance the tensile strength of OPSFRC to be applied as structural members for special usage which requires high tensile strength. The high tensile strength OPSFRC was tested for mechanical properties, toughness and flexure beam testing. The results show that the synthetic fibers including polypropylene and nylon fibers produced slight increments on the mechanical properties of OPSFRC without significant changes in density. On contrary, steel fibers of aspect ratio 65 outperformed other fibers to produce the highest compressive and flexural strength of 47 MPa and 7 MPa, respectively. Therefore steel fiber of aspect ratio 65 with amount up to 1% was added in the OPSC beams to investigate the flexural and torsional behaviors of OPSFRC beams. The experimental results reported that the increase in the fiber volume resulted in a higher enhancement of the flexural, torsional and cracking resistance of the OPSFRC beams. The OPSFRC beams reinforced with 1% steel fiber show significant increment in flexural and torsional toughness compared to the plain OPSC specimens. OPSFRC beam with 3% steel fibers produced high tensile strength with flexural strength of 18 MPa. The flexural behaviors of high tensile strength OPSFRC showed drastic improvement in moment capacity and cracking resistance compared to OPSFRC beam with 1% steel fiber. It can be concluded that the addition of steel fiber up to 3% enabled the production of high tensile strength OPSFRC which is suitable for structural application.